2017
DOI: 10.1002/jum.14266
|View full text |Cite
|
Sign up to set email alerts
|

Economical Sponge Phantom for Teaching, Understanding, and Researching A‐ and B‐Line Reverberation Artifacts in Lung Ultrasound

Abstract: This project evaluated a low-cost sponge phantom setup for its capability to teach and study A- and B-line reverberation artifacts known from lung ultrasound and to numerically simulate sound wave interaction with the phantom using a finite-difference time-domain (FDTD) model. Both A- and B-line artifacts were reproducible on B-mode ultrasound imaging as well as in the FDTD-based simulation. The phantom was found to be an easy-to-set up and economical tool for understanding, teaching, and researching A- and B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In the literature, alternative experimental models able to generate B-lines have been reported. Differently than the model presented in this study these models were based on gelatin phantoms containing large air bubbles (mm size) obtained by manual injection of air by means of a syringe 21 , sponges 22 , 23 and foams 24 .…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, alternative experimental models able to generate B-lines have been reported. Differently than the model presented in this study these models were based on gelatin phantoms containing large air bubbles (mm size) obtained by manual injection of air by means of a syringe 21 , sponges 22 , 23 and foams 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Models have been created with plastic phantoms or a wet sponge with or without pork ribs, but also simply using a hand with a wet foam. [94][95][96][97]…”
Section: Standardised Protocol For Functional Lus: the Safe Algorithmmentioning
confidence: 99%
“…A lung phantom model was constructed, for which the lung tissues and the pleural fluid layer were modeled by sponges and a thin layer of US transmission gel. Low‐cost sponges have been used in multiple studies to model a lung . The lung has a spongy porous structure; sponges, as demonstrated by Blüthgen et al, can reproduce A‐ and B‐line artifacts observed in lung US images.…”
Section: Methodsmentioning
confidence: 99%
“…Low‐cost sponges have been used in multiple studies to model a lung . The lung has a spongy porous structure; sponges, as demonstrated by Blüthgen et al, can reproduce A‐ and B‐line artifacts observed in lung US images. A polyurethane sponge was reported to be similar to a lung in acoustic impedance, porosity, sound velocity, etc, by Soldati et al Cellulose sponge pieces likewise were used by Molinari et al for pulmonary edema modeling.…”
Section: Methodsmentioning
confidence: 99%